Developing a Steam and Tri Hita Karana Comic to Improve Fifth-Grade Elementary School Students' Science Literacy - Nengah Kadek Selamet; I Gede Margunayasa; Dewa Bagus Sanjaya (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2026)
The current problems are low student science literacy and fading cultural values. This research aims to develop learning media in the form of STEAM-infused comics containing Tri Hita Karana values to improve the science literacy of fifth-grade students on the ecosystem harmony material at SD Negeri 6 Penatih. Developmental research method using the ADDIE model. Data collection instruments used questionnaires to test validity, practicality, and effectiveness. The research results show that this comic meets excellent criteria, as evidenced by the validation results from content experts, media experts, design expert, and language experts. The practicality test conducted by teachers showed very satisfactory results with a percentage of 98%. The practicality test results for students obtained a percentage of 94.51%, indicating that this comic is very practical and well-received by students. The effectiveness test results thru pretest and posttest showed a significant improvement in students' science literacy with a significance value (p < 0.001) and a high effect size (Cohen's d = 3.208). In conclusion, STEAM-loaded comics and Tri Hita Karana are effective in improving the science literacy of fifth-grade elementary school students. The implications are positive, such as increased student interest in science thru culturally relevant approaches, as well as potential long-term impacts in the form of improved science literacy. The novelty of this research lies in the integration of steam and Balinese local wisdom with the help of sophisticated AR so that the media becomes more contextual, real, interesting, and students' literacy increases.